56 'A Closed-Loop Audit on The Appropriateness of Urine Testing Carried Out on Surgical Patients in The Acute Surgical Unit in University Hospital Limerick as Compared with Hospital Guidelines'. (12th October 2021) - Murphy, B; Amin, K; Ali, N
Abstract: Aim: The acute surgical unit (ASU) in University Hospital Limerick (UHL) has a high turnover of patients of all surgical specialties, many of whom are sent home without the need for admission or follow-up. Urinalysis is very accessible, and is carried out on many patients, prior to them being seen by a doctor. Inappropriate urinalysis sets off a cascade of inappropriate urine culture, antimicrobial treatment and a waste of resources and time of nursing, medical and laboratory staff. We aim to identify and reduce inappropriate testing. Method: The notes of all ASU patients during a one-week period were analysed using the 'Therefore Navigator' application, where all patient notes are scanned on leaving the ASU. Data relating to presenting complaint, presence or absence of urinary symptoms and abdominal pain, and urine dipstick and culture results (if performed) was collected for each patient. The results were compared with UHL guidelines on testing, an information sheet was designed and placed in ASU, and an education session for nursing staff was carried out. The second cycle was performed one month later. Results: In the first cycle, 68% of the 99 ASU patients had urinalysis, and 48% had urine culture performed. Of cultures performed, only 23 of 47 (49%) were deemed indicated according to the guidelines. In the second cycle, 39% had urinalysis. 28% had urine cultured, 79% of these were deemed to have been indicated. Conclusions: Inappropriate urine testing in the ASU decreased following teaching for nursing staff, together with an information leaflet being placed in the ASU.